Business managers and moral sanctuaries - Konrad, Armin Richard (Journal of business ethics, 1982)
‘Moral Sanctuary’ is used in this paper as a metaphor for any theory which makes actions immune from moral criticism. Three arguments favoring moral sanctuaries for business activities are countered. Two of the arguments rest on faulty analogies. One compares business activities to games, another to the behavior of machines. The third rests on the claim that business is a unique activity. This position is rejected by a reductio ad absurdum argument; it entails the immunity of all professional activities from moral judgment. I argue that business managers are accountable to the combined requirements of professionalism and democratic citizenship, notions which are briefly described at the conclusion of the paper.